Host-derived glycans serve as selected nutrients for the gut microbe: human milk oligosaccharides and bifidobacteria*. Issue 4 (2nd April 2016) - Katayama, Takane
Abstract : Lactation is a common feeding strategy of eutherian mammals, but its functions go beyond feeding the neonates. Ever since Tissier isolated bifidobacteria from the stool of breast-fed infants, human milk has been postulated to contain compounds that selectively stimulate the growth of bifidobacteria in intestines. However, until relatively recently, there have been no reports to link human milk compound(s) with bifidobacterial physiology. Over the past decade, successive studies have demonstrated that infant-gut-associated bifidobacteria are equipped with genetic and enzymatic toolsets dedicated to assimilation of host-derived glycans, especially human milk oligosaccharides (HMOs). Among gut microbes, the presence of enzymes required for degrading HMOs with type-1 chains is essentially limited to infant-gut-associated bifidobacteria, suggesting HMOs serve as selected nutrients for the bacteria. In this study, I shortly discuss the research on bifidobacteria and HMOs from a historical perspective and summarize the roles of bifidobacterial enzymes in the assimilation of HMOs with type-1 chains. Based on this overview, I suggest the co-evolution between bifidobacteria and human beings mediated by HMOs. Graphical abstract: Symbiosis and co-evolution between bifidobacteria and humans, mediated by human milk oligosaccharides with a type-1 chain.